Attitudes of Registered Nurses Towards Nursing Students in Clinical Settings at the University of Calabar Teaching Hospital, Calabar, Cross River State, Nigeria - Fred Grace Wayas; Allahnanan Emmanuel; Ndukaku Nwakwue; Fred Ernest Wayas (Journal of Multidisciplinary Science: MIKAILALSYS, 2025)
Clinical exposure is fundamental to nursing education, offering student nurses critical opportunities for skill acquisition, professional socialization, and practical application of theoretical knowledge. This study examines the attitudes of registered nurses toward nursing students during clinical placements at the University of Calabar Teaching Hospital (UCTH), Calabar, Cross River State, Nigeria. Adopting a descriptive cross-sectional design, data were collected from 240 registered nurses across eight clinical wards using a structured, self-administered questionnaire. Descriptive and inferential statistical analyses were conducted to evaluate attitude patterns and associated influencing factors. The results indicate that a majority of registered nurses exhibited positive attitudes, characterized by a willingness to mentor, supervise, and collaborate with nursing students. However, certain challenges were identified, including perceived increases in workload, student absenteeism, and concerns about student adherence to professional and ethical standards. Key determinants of nurse attitudes included the perceived clinical competence, communication ability, and adherence to professional dress codes among students. The study underscores the need for structured mentorship programs, regular workshops on ethical conduct, and more clearly defined internship frameworks to strengthen the clinical learning environment. Enhancing nurse-student interactions in clinical settings is essential for improving the quality of nursing education and ensuring the readiness of future nursing professionals for practice.